Analyzing Learning Media for The Elderly - Edwin Nugraha; Dyoys Anneke Rantung; Lamhot Naibaho (International Journal Labs, 2023)
The church must be able to accommodate the spiritual needs of the elderly. The church needs to pay attention to learning media for the elderly so that they can understand the preaching of God's Word well and even feel closer and calmer with God in their daily lives. The purpose of this study is to explain the essence and purpose of using learning media in the context of the elderly, understand the special characteristics and challenges faced in using learning media for the elderly, provide practical guidance in applying various types of learning media for the elderly, analyze the use of special learning media for the elderly, and explore its implementation in the context of Christian Education. The chosen research methodology is literature research, which involves examining and incorporating ideas and viewpoints from various authors of books and articles. These sources serve as valuable references for our study in the field of literature. From the research findings, it can be concluded that educators or pastors need to have a deep understanding of the background of learning problems experienced by the elderly. This is important so that they can choose the type and characteristics of learning media that are appropriate and suitable for the elderly. Regardless of the form of learning media chosen, it is important to pay attention to the needs according to the physical and psychological conditions of the elderly.